Efficacy of farmer field schools in achieving participatory technology development among smallholder farmers in the Hoima district, Uganda - Mwesigwa, David (Goodwood Publishing, 2021)
Purpose: This study investigated the efficacy of FFS for participatory technology development among smallholder farmers in Hoima district, Uganda. It is anticipated that by making FFS concrete, household food security will be enhanced. Research methodology: The study utilised primary data, which was collected using a self-administered questionnaire. While 120 respondents were sampled, 103 responded, generating a response rate of 85.83%. This was an excellent response seeing that it merited above 75%. The researcher administered all questionnaires in one month. Results: From the findings indicate that PTD is more desirable in the Hoima district. In addition, the construct of the ability to solve problems from time to time indicates that problem-solving is very desirable for PTD in the Hoima district. The results suggest a positive correlation between FFS and PTD among the study population, indicating that a unit-change in the FFS constructs will lead to a proportionate change in the constructs of PTD in the same direction. This implies that improving FFS quality by a single unit will translate into progressive improvement in PTD in the Hoima district. This study also suggests that FFS alone has a strong positive influence on PTD in the Hoima district. Limitations: This study merely covered farmer-field schools, yet several interventions aim to raise the quality of agriculture in Uganda, such as National Agricultural Advisory Services and Emyoga. Contribution: This study contributes to the deeper understanding of what ought to be done to improve the quality of farming in Uganda.